Chunibyo: Psychological Disorders in Anime Aura: Maryuinko Ga Saigo No Tatakai - Ida Ayu Laksmita Sari; Renny Aggraeny (Research and Community Services Institutes of Udayana University, 2017)
This study discusses the behavior of the characters in anime Aura: Maryuinko ga Saigo no Tatakai who are suffering from chunibyo psychological disorders. Chunibyo? behavior can occur because of excessive admiration of animated character so that one can be dissolved in an imaginary world. Through the psychological theory of literature and psychology of personality this paper analyzes the behavior of chunibyo in Anime Aura: Maryuinko ga Saigo no Tatakai, discrimination exercised by the local community and how to cure chunibyo psychological disorders. The results showed that the characters in anime Aura: Maryuinko ga Saigo no Tatakai suffer from psychological disorder of chunibyo jakigankei type characterized, among others, by possession of another identity, consider themselves super hero, come from other world, and the rejection of the environment. Discriminatory behavior which is the most widely accepted by the patient of chunibyo is ijime (bullying). In this anime, the characters can be cured in many ways by involving them into the fantasy world and taking them back to the real world.